Teachers’ Core Behavioral Competencies and School Performance: Basis for School Development Plan (American Journal of Arts and Human Science, 2024)
Teachers’ core behavioral competencies play a crucial role in shaping the learning experience and academic outcomes of students that will reflect the school performance. The teachers in the Division of Misamis Oriental had a hard time developing their core behavioral competencies. The respondents were the three hundred forty-eight (348) public elementary teachers in the Division of Misamis Oriental. The research instrument was the survey questionnaire on core behavioral competencies and the school performance. Descriptive research design was used to interpret and analyze data such as mean and standard deviation to describe the level of core behavioral competencies. Pearson-r moment Correlation Coefficient to determine the significant relationship between independent and dependent variables. The findings revealed that the teachers have a very high level of behavioral competence in Self- Management and least in Service Orientation. The secondary data revealed a decrease of 0.99 percent during the enrollment of SY 2022-2023 which means that they have a negative performance during this school year. However, there is no significant relationship between core behavioral competencies in all variables and all of the school performance indicators. It is concluded that teachers in the Division of Misamis Oriental have a high level of behavioral competence in terms of Service Orientation. It is recommended that teachers should be given the opportunity to promote advocacy for men and women empowerment and update themselves in participating the office mission and vision mandates.